Administrative Skills in the 21st Century and Effectiveness in School Administration at the Nakhon Mak Khaeng School Network Center under the Udon Thani Primary Educational Service Area Office 1 - Ajnukarnsomruk, Pornpitcha; Kumhom, Naitawan (Journal of Humanities and Social Sciences, Rajapruk University, 2024)
The purposes of this research were to study 1) the level of administrative skills in the 21st century 2) the level of effectiveness in school administration 3) the relationship between administrative skills in the 21st century and the effectiveness in school administration of the Nakhon Mak Khaeng School Network Center under the Udon Thani Primary Educational Service Area Office 1. The sample were 147 personnel from the Nakhon Mak Khaeng School Network Center. The instrument used was a questionnaire. Data were analyzed using percentages, mean, and standard deviations and find the relationship using Pearson’s product moment correlation coefficient. The results showed that: 1) Overall, management skills in the 21st century were at a high level. Considering each aspect, it was found that number 1 was management and adaptation skills, followed by communication and cooperation skills and the last ranking is knowledge skills and responsibility. 2) Overall, management effectiveness was at a high level. Considering each item, it was found that number 1 was the ability to solve problems within the educational institution, followed by the ability to develop students to have higher academic achievement, ability to develop students to have positive attitudes, and the last ranking was the ability to change and develop educational institutions. 3) Relationship of administrative skills in the 21st century with effectiveness in school administration of the Nakhon Mak Khaeng School Network Center Under the jurisdiction of the Udon Thani Primary Educational Service Area Office 1, overall, there was a positive relationship at the moderate level, with statistical significance at the .01 level. And when considering each aspect, it was found that. Management skills in the 21st century were positively correlated with management effectiveness, sorted by correlation coefficient. The first place was the ability to develop students to have higher academic achievement (r=0.55). Equal to the ability to develop students to have a positive attitude (r=0.55) It was equal to the ability to modify and develop educational institutions (r=0.55), followed by the ability to solve problems within the educational institutions (r=0.54), respectively.